Quality of life, sense of coherence and levels of sedentarism of faculty and staff from the Presbítero Benjamín Núnez, U.N.A. - Ureña Bonilla, Pedro (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2008)
The aim of this study was to analyze the quality of life of faculty and staff of the Presbítero Benjamín Núñez Campus of Universidad Nacional (UNA, Costa Rica) as well as to assess the influence of two factors, sense of coherence and physical exercise, in the quality of life of the subjects.  A group of 37 faculty members and 30 staff members participated in the study.  The SF-36 Questionnaire, the Sense of Coherence Scale, and a survey to measure physical exercise habits were used.  In general, results showed a relatively good quality of life and similar scores were found in the Sense of Coherence Scale.  Additionally, significant connections were found between certain factors related to sense of coherence and quality of life.  Data confirmed that persons who practice physical exercise have a better quality of life than those who are not physically active.  It was concluded that, although quality of life and sense of coherence were relatively good, new proposals must be designed and implemented to improve both aspects.  In this sense, physical exercise proved to be one of the pillars in the development of innovative proposals aimed at bettering health in university employees, all of this within the “Healthy Universities” concept.